In-Vehicle Visible Light Communications Data Transmission System Using Optical Fiber Distributed Light: Implementation and Experimental Evaluation - Cătălin Beguni; Alin-Mihai Căilean; Sebastian-Andrei Avătămăniței; Eduard Zadobrischi; Raul Stoler; Mihai Dimian; Valentin Popa; Bastien Béchadergue; Luc Chassagne (Sensors, 2022)
Visible light communications emerges as a promising wireless communication technology that has been found suitable for numerous indoor and outdoor applications. In this article, a new in-vehicle VLC system is designed, implemented, and experimentally evaluated. The purpose of this new system is to provide car passengers with optical wireless communications. The proposed system consists of a VLC emitter integrated into the vehicle’s ambient lighting system and a mobile VLC receiver. Unlike any previous works, this article proposes a VLC emitter in which the light from a 3 W LED is distributed on a 2 square meter surface using 500 optical fibers whose main purpose is a decorative one. The proposed prototype has been implemented on a car and evaluated in relevant working conditions. The experimental evaluation of the proposed system has demonstrated the viability of the proposed concept and showed a data rate of 250 kb/s while providing a BER lower than 10−7. As far as we know, the proposed concept is totally new in the VLC literature, opening a new area of utilization for VLC technology: using VLC with optical fiber distributed light.